1999
DOI: 10.1002/(sici)1096-9071(199902)57:2<179::aid-jmv16>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Undenatured parvovirus B19 antigens are essential for the accurate detection of parvovirus B19 IgG

Abstract: Recombinant versions of parvovirus B19 capsid proteins VP1 and VP2 are used for immunodiagnostic assays for detection of antiviral antibodies. The immune response to B19 is characterized by a gradual loss of antibodies directed against linear epitopes of VP2. A similar occurrence for antibodies raised against VP1 protein would represent a limitation to serological assays incorporating denatured versions of either viral antigen. Four detection systems for B19 Ig detection have been developed, including an IgG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 19 publications
(23 reference statements)
4
57
0
4
Order By: Relevance
“…Safe cellular blood products are to be administered to pregnant women (except in the case of transfusions given during birth), patients with congenital or acquired haemolytic anaemia who have no detectable antibodies to B19 and patients with cellular immunodeficiency who have no detectable antibodies to B19. 24 It is still unclear whether B19 NAT screening of blood products should be envisaged. Future studies of transmissibility of B19 by transfusion should, when possible, take into account not only the level of B19 in the blood product, its overall transfused dose, but also, equally importantly, the presence of anti-B19 antibodies, their potency and titre in the blood product, the immune status of the recipient, and recipient's B19 infection history, anti-B19 status and viral persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Safe cellular blood products are to be administered to pregnant women (except in the case of transfusions given during birth), patients with congenital or acquired haemolytic anaemia who have no detectable antibodies to B19 and patients with cellular immunodeficiency who have no detectable antibodies to B19. 24 It is still unclear whether B19 NAT screening of blood products should be envisaged. Future studies of transmissibility of B19 by transfusion should, when possible, take into account not only the level of B19 in the blood product, its overall transfused dose, but also, equally importantly, the presence of anti-B19 antibodies, their potency and titre in the blood product, the immune status of the recipient, and recipient's B19 infection history, anti-B19 status and viral persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this comes from the results obtained following Western blot analysis of anti-B19V NS1 IgM positive specimens, whereby SDS denaturation and DTT presence apparently lead to the disruption of conformationally relevant epitopes with concomitant false negative detection of anti-B19V NS1 IgM.. Since it has been previously shown that all specimens that are anti-B19V VP2 IgM positive by microplate ELISA also test positive by Western blot (Kerr et al, 1999), which used a similar method for antigen electrotransfer onto nitrocellulose, it is unlikely that methodological differences account for the observed difference with respect to anti-B19V NS1 IgM detection between microplate ELISA and Western blot immunoassay. It is notable that no specimen tested was anti-B19V VP2 IgM negative and anti-B19V NS1 IgM positive, which is not unexpected given the antigenic nature of viral capsid proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these antigens have been expressed in eukaryotic expression systems in order to assess their potential use as diagnostic reagents for B19V infection (Brown et al, 1990). This work has culminated in the recent demonstration of the absolute requirement for intact capsid structure for optimal detection of anti-B19V VP2 IgG (Kerr et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 164 potentially cross-reactive specimens tested in this study, only 6 specimens were reactive when equivocal results are included as false positive. These EBV (N= 2) and mycoplasma (N= 1) specimens which were reactive or equivocal in the immunoassay were also tested using a parvovirus B19 IgM IFA and Western blot assay (Kerr et al, 1999). The EBV specimens were found to be strongly reactive in both assays.…”
Section: Discussionmentioning
confidence: 99%
“…Capsid purification has been previously described (Kerr et al, 1999) and the resultant capsid VP2 was biotinylated using N-hydroxysuccinimid-obiotin at a 50:1 (reagent:protein) molar ratio.…”
Section: Antigen Production Purification and Modificationmentioning
confidence: 99%